Los eva y su aporte en las metodologías activas en el segundo semestre de la Carrera de Educación Básica periodo abril- septiembre 2022 - Gómez Fernández, Angie Isabel (2022)
The following project for degree whose theme has to do with the EVA (Virtual Learning Environment) and active methodologies, aims to analyze the contribution of these variables in education maintained by students in the second semester of the basic education career, which was designed through a quantitative study through the first level called descriptive which allows the use of a wide range of techniques that facilitate the collection of information through the progress of the documents, such as the questionnaire that belongs to the survey, and for which 85 participants were selected as a sample, all of them university students, who using the deductive method could analyze the information collected, concluding that the main pillar of education and its virtuality is the use of Moodle in the Technical University of Babahoyo, so it is a contribution in active learning strategies such as problem-based methodology, which is an educational resource that keeps the student active, always looking to solve the research raised by the teacher, so the location of articles in the virtual classroom has contributed significantly to the development of learning, after this It is arrived as a recommendation that it is to improve the gap that separates from the young people who fully know the virtual learning environment the number that is 30% is necessary to include it within the teaching through a talk or extra training that allows them to understand the benefits of virtual education without replacing the traditional one.